The inner reformation of the sciences: an ambiguity in the radically orthodox thought of John Milbank? - D. F. M. Strauss (Acta Theologica)
Although both Radical Orthodoxy and Reformational Philosophy question the autonomy of theoretical reason, the views of prominent representatives of Radical Orthodoxy do not enable an inner reformation of the non-theological academic disciplines. Whereas Radical Orthodoxy holds that philosophy is concerned with being as such, theology investigates the ground of being, and being in respectu Dei. Reformational Philosophy questions theology as “queen of the sciences” and holds that every creature has to be “related” to God. Milbank contemplates the idea of a Christian sociology, by considering the church as a distinct society (altera civitas), but considers it to be silly to talk of a Christian mathematics. An alternative idea of Christian scholarship is advanced in opposition to Milbank’s classical Thomistic view, namely that theology has to preserve and fulfil philosophy, echoing the Scholastic adage that grace does not eliminate nature, but perfects it (gratia naturam non tollit, sed perficit).